Бухгалтерський облік та оподаткування доходів підприємства за матеріалами ПрАТ «Київський електровагоноремонтний завод» - Руденко, Нікіта Андрійович; Rudenko, Nikita Andriyovych (Ірпінь, 2023)
У дипломній роботі розкрито дослідження стану бухгалтерського обліку та оподаткування доходів підприємства і розробка пропозицій щодо удосконалення методики обліку та формування фінансової звітності. За результатами дослідження сформульовані пропозиції щодо удосконалення бухгалтерського обліку та оподаткування доходів підприємства та їх запровадження на «ПрАТ «Київський електровагоноремонтний завод», а саме, елементи облікової політики в частині формування доходів.

The study of the state of accounting and taxation of the company's income and the development of proposals for the improvement of accounting methods and the formation of financial statements are disclosed in the thesis. Based on the results of the research, proposals were formulated regarding the improvement of accounting and taxation of the company's income and their implementation at PJSC "Kyiv Electric Car Repair Plant", namely, the elements of the accounting policy in terms of income generation.
Accounting and taxation of the company's income according to the materials of PJSC "Kyiv electric car repair plant"
Keywords: доходи; облік доходів; оподаткування доходів; податок на прибуток; система оподаткування.; income; income accounting; income taxation; income tax; taxation system